2014
DOI: 10.15252/embj.201488466
|View full text |Cite|
|
Sign up to set email alerts
|

Tubulin glycylases are required for primary cilia, control of cell proliferation and tumor development in colon

Abstract: TTLL3 and TTLL8 are tubulin glycine ligases catalyzing posttranslational glycylation of microtubules. We show here for the first time that these enzymes are required for robust formation of primary cilia. We further discover the existence of primary cilia in colon and demonstrate that TTLL3 is the only glycylase in this organ. As a consequence, colon epithelium shows a reduced number of primary cilia accompanied by an increased rate of cell division in TTLL3-knockout mice. Strikingly, higher proliferation is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
90
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(108 citation statements)
references
References 48 publications
5
90
0
Order By: Relevance
“…As glycylation in the mouse retina is catalysed exclusively by TTLL3, we investigated the role of this PTM in our TTLL3-knockout (Ttll3 −/− ) mouse (Bosch Grau et al, 2013;Rocha et al, 2014). We first confirmed the absence of TTLL3 expression in retina of Ttll3 −/− mice at different developmental stages, and demonstrated that TTLL8 expression remained virtually undetectable, similar to in the wild-type situation (Fig.…”
Section: Absence Of Tubulin Glycylation Leads To Hyperglutamylation Imentioning
confidence: 78%
“…As glycylation in the mouse retina is catalysed exclusively by TTLL3, we investigated the role of this PTM in our TTLL3-knockout (Ttll3 −/− ) mouse (Bosch Grau et al, 2013;Rocha et al, 2014). We first confirmed the absence of TTLL3 expression in retina of Ttll3 −/− mice at different developmental stages, and demonstrated that TTLL8 expression remained virtually undetectable, similar to in the wild-type situation (Fig.…”
Section: Absence Of Tubulin Glycylation Leads To Hyperglutamylation Imentioning
confidence: 78%
“…Since TTLL10 is inactive in humans, human sperm flagellar tubulins are monoglycylated [54], and the absence of long chain polyglycylation does not affect ciliary motility [56], so the functional significance of extended polyglycine chains is uncertain. However, a knockout of TTLL3 eliminates all tubulin glycylation in the colon, where TTLL3 is the only glycylase expressed [57]. This absence of glycylation led to reductions in primary cilia and enhanced carcinogenesis in the colon, suggesting that glycylation of tubulin may play a role in the maintenance of primary cilia and cell proliferation.…”
Section: Polyglutamylation and Polyglycylation Of Tubulin In Mtsmentioning
confidence: 99%
“…Monoglycylation is ubiquitous in ciliated tissues, whereas only a subset contains polyglycylated microtubules (61). Glycylation is important for the stability, length, and function of motile cilia (7,62,63), the formation and maintenance of primary cilia, and control of cell proliferation (64).…”
Section: Glycylationmentioning
confidence: 99%